Development of thin films of thermographic phosphors for spatial resolved temperature measurements using sputtering techniques (2013)
Abstract: Two thermographic phosphors materials for surface temperature measurements, praseodymium-doped calcium titanate, CaTiO3:Pr3+, and chromium-doped gadolinium gallium oxide, Gd3Ga5O12:Cr3+, have been successfully deposited on stainless steel substrates by radio frequency magnetron sputtering. For the sputtering process, phosphor targets were prepared using sol-gel combustion (for CaTiO3:Pr3+) and solid-state reactions (for Gd3Ga5O12:Cr3), combined with high temperature sintering. The physical, chemical and luminescence properties of the phosphor films have been evaluated using X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS) and laser diagnostics. The results showed that the luminescence features of the thin films were restored by heat treatment after the sputtering deposition. The CaTiO3:Pr3+ film showed low temperature sensitivity of its luminescence lifetime and poor precision of the temperature determination, which could limit its thermographic functionality. Contrary, the Gd3Ga5O12:Cr3+ film exhibited appropriate temperature sensitivity with adequate precision of the temperature determination, proving to be suitable for thermographic applications. An evaluation of the two-dimensional luminescence characteristics of the Gd3Ga5O12:Cr3+ thin film revealed spatial inhomogeneities in the luminescence lifetime of the film. A study on Gd3Ga5O12:Cr3+ powders samples, varying the doping concentration and co-doping with cerium, was included with the aim of increasing the understanding about the luminescence characteristics of this phosphor. These results showed that increasing the Cr doping concentration only changes significantly the luminescence lifetime for concentrations above 1 mol%, while temperature sensitivity and precision of the temperature determination are maintained. Co-doping with small amounts of cerium reduces the afterglow of the Gd3Ga5O12:Cr3+ phosphor. However, an excess of cerium could significantly affect the luminescence properties, resulting in poor precision of the temperature determination